Infecção por riquétsias em carrapatos de aves da região do Cerrado e Pantanal Mato-grossense, Centro-Oeste, Brasil - Ramos, Dirceu Guilherme de Souza (2016)
The involvement of different species of ticks and wild animals, such as birds, play an important role in the epidemiology of tick-borne diseases. Birds may serve as reservoirs for some tick-borne diseases, and may carry and spread hematophagous ectoparasites mechanically. This study aimed to show the diversity of ticks on birds and molecular detection of rickettsial infection in ticks from Pantanal and Cerrado, two similar Brazilian biomes characterized by hydrological seasons. During two years, August 2012 to May 2014, ticks were collected on birds and from the environment in total of 14 visits for collecting samples, distributed in all hydrological seasons. A total of 674 birds were captured representing 113 species from 26 families. In total, 71 birds were parasitized (10.5%), and 155 ticks of the following 7 tick species (in decreasing order of prevalence) were identified: Amblyomma longirostre (Koch), Amblyomma nodosum Neumann, Amblyomma cajennense Fabricius, Amblyomma calcaratum Neumann, Ornithodoros mimon Kohls, Clifford & Jones, Amblyomma ovale Koch, and Amblyomma triste Koch. Among free-living ticks collected in the environment, Amblyomma cajennense sensu lato (s.l.) was the most common. Further, herein we described, for the first time, occurrence of Ornithodoros mimon on birds and of Amblyomma triste on Passeriformes in Brazil. Molecular analyses revealed that six A. longirostre ticks were infected by Candidatus ‘Rickettsia amblyommii’, whereas one A. nodosum was infected by a Rickettsia parkeri-like agent, previously reported as Rickettsia sp. strain NOD. Spotted fever group (SFG) agents were, for the first time, reported in ticks from birds captured in Pantanal biome, and the potential involvement of these agents as human pathogens should be considered in further studies.